Association of Ishii test scores with pneumonia in stable schizophrenic subjects - Yang, Qin; Huang, Sha; Chen, Ming; Zhu, Tian; Li, Qiuxia; Chen, Xiaoyan (Frontiers in Psychiatry, 2022)
Aim: Here, we investigated the relationship between the sarcopenia-indicating Ishii test score and pneumonia risk in stable schizophrenia patients. Method: This is a prospective investigation involving schizophrenic inpatients from two mental health centers in western China. Patient baseline information was gathered over 1 month from September 1-30 in 2020. All pneumonia-related patient information, including diagnosis and treatment, were acquired over 1 year between October 2020 and October 2021. A threshold value, recommended by Ishii et al., was employed for the sarcopenia screening of schizophrenia patients. The relationship between the Ishii test score and pneumonia risk in schizophrenia patients was analyzed using logistic regression analysis. Result: This study recruited 232 males and 107 females with schizophrenia over the age of 50 and older. During a 1-year follow-up, 4 patients (3 males, 1 female) developed pneumonia within 1 week of schizophrenia relapse, so these patient were eliminated from analysis. Finally, data were collected for 335 patients. The pneumonia incidences were 29.3% in males and 14.2% in females. Our analysis confirmed that, compared to the male schizophrenia patients with Ishii test score <105 (non-sarcopenia), those with Ishii test ≥105 (sarcopenia) exhibited an elevated pneumonia risk (OR=2.739, 95%CI: 1.406-5.333). Following confounders adjustment, an Ishii test score ≥ 105 still remained a risk factor for pneumonia (OR=2.064, 95%CI: 1.029-4.143). Among females with schizophrenia, the Ishii test score was not associated with pneumonia risk. Conclusion: Herein, we demonstrated that the Ishii test score ≥105 was strongly associated with pneumonia risk in stable schizophrenic male patients.